Profesionalisme Guru MI Dalam Menerapkan Strategi Pendidikan Matematika Realistic (PMR) Di Masa Pandemic-19 - Mulyono Mulyono; Nika Trisnawati; Komayanti Komayanti; Nirmala Kokop (Universitas Sarjanawiyata Tamansiswa, 2022)
Being a professional teacher is the main thing that is the key to a quality education in the future, especially during the current covid-19 pandemic. The formulation of the problem in this study is how the professionalism of MI teachers in maximizing mathematics learning by applying realistic mathematics learning strategies (PMR) the time of the covid-19.the methods and techniques of data mining in this study using qualitative research with descriptive methods the data of this study were sourced from an teacher of MI Roudlotul Khuffadz grade IV, all data collection or instruments used in this study were interviews professionalism or efforts of elementary school teachers (SD/MI) in maximize mathematics learning by using realistic mathematics learning strategies during the covid-19 pandemic.the results of the study showed that the teacher of MI Roudlotul Khuffadz grade IV was professional incarrying out his duties as a mathematics teacher during the covid-19 pandemic.